Radio jingles and the development of healthy eating habits among university students - Kyangchat, Samaila Maria; Joseph, Ayodele B. (Journal of Language and Pragmatics Studies, 2023)
This study examined how radio jingles affects the development and ability to form good eating habits amongst undergraduate students of mass communication department, Kaduna state university. It looks at how radio jingles might improve the understanding, and encourage the adoption of good eating habits amongst students of mass communication department, thereby raising awareness and understanding on healthy eating habit. The Social Cognitive Theory (SCT) was adopted as the underlying theoretical framework, while the empirical analysis of scholarly articles, books reports that address the influence of radio jingles on healthy eating habit was adopted as the methodology. Amongst other things, the study found that; the exposure of radio jingles in promoting healthy eating habit led to increase in tension amongst mass communication student to engage in healthy eating behavior. The study concludes that; Radio jingles have the potentials to play a significance role in the development and promotion of healthy eating habit among University students. As such it is recommended that collaboration with local radio stations will enhance the wide dissemination of jingles to reach out to a large audience. Thus, efficacy of jingles in the development of healthy eating habit can be maximized by adopting a multi-channel approach, which includes radio broadcasts, social media, and websites.